Synergistic mechanism of botanical pesticide camptothecin encapsulated in a nanocarrier against fall armyworm: Enhanced stability and amplified growth suppression - Xinzheng Huang; Xueqi Ni; Huali Li; Ying Wei; Zeng Wang; Cong’ai Zhen; Meizhen Yin; Jie Shen; Wangpeng Shi; Yongjun Zhang; Shuo Yan (Ecotoxicology and Environmental Safety)
Botanical pesticides are one of the most promising alternatives to synthetic insecticides for green pest management. However, their efficacies must be further improved to meet real needs. Here we designed a nanoscale camptothecin (CPT) encapsulated in a star polycation (SPc) and determined its bioactivity against a devastating agricultural pest, Spodoptera frugiperda. The self-assembly of CPT/SPc complex was mainly driven by hydrogen bonding and Van der Waals forces to decrease the particle size from 789 to 298 nm. With the help of SPc, the contact angle of CPT decreased from 116° to 92° on maize leaves, and its retention was increased from 5.53 to 11.97 mg/cm2. The stability of SPc-loaded CPT was also improved in an alkaline environment, which is beneficial for its acting in lepidopteran insect guts. The CPT/SPc complex had stronger larvicidal activity and ovicidal activity against S. frugiperda than CPT alone, led to more complex transcriptomic changes in larvae, and had obvious adverse impacts on the activities of two digestive enzymes. Our findings demonstrated that the encapsulation of CPT by SPc-based nanodelivery system enabled better insecticidal activities against S. frugiperda, which holds great promise for the development of more efficient and sustainable pest control strategies to meet the demands of modern crop protection.